PENINGKATAN KAPASITAS PENGELOLA PERIKANAN WPPNRI-718 TERKAIT EAFM: PEMBELAJARAN DI KABUPATEN KEPULAUAN ARU - Abrahamsz, James; Makailipessy, Marvin M; Ayal, Frederik Willem; Tuapetel, Friesland (Balobe: Jurnal Pengabdian Masyarakat, 2022)
The implementation of fisheries management in Indonesia is guided by EAFM concept. Aru Islands, an area in WPPNRI-718 that contributes fishery production in Maluku and Indonesia significantly. Fishery activities dynamic in this region are high, requiring the strengthening of management capacity. Fisheries managers in this area do not yet have a strong understanding and capacity in implementing EAFM. Strengthening fisheries managers capacity was mandated by the Minister of Maritime Affairs and Fisheries Regulation Number 9 of 2015, as well as responding to the need for EAFM competency standards. The activity was attended by 14 participants from 11 institutions in Dobo. Five stages process including: pretest; presentation of introductory material and the six EAFM domains as well as discussions; field trip and data collection; analysis, results presentation, formulation of recommendations; and post test. The results showed an increase in EAFM knowledge around 92.86%, with the level of understanding change of 71.43%